Maternal Role: A Concept Analysis - Sharmila Shrestha; Kumiko Adachi; Marcia A Petrini; Sarita Shrestha (Mashhad University of Medical Sciences, 2019)
Background & aim: Childbirth and motherhood is a rewarding experience. A mother needs to adapt to her new maternal role after childbirth. The aim of the present study was to clarify the defining attributes of maternal role and identify its antecedents and consequences. Methods: As suggested by Walker and Avant, the present concept analysis utilized the eight-step methodology. A search of the English literature was accomplished by searching the databases including CINAHL, Google Scholar, PubMed, and Medline, from 1994 to 2016 using the keywords of maternal role, maternal identity, maternal role attainment, transition to motherhood, and motherhood. Results: The antecedences of maternal role were pregnancy, maternal identity, maternal behaviors, adjustment to child-rearing, and bonding with the child.  The defining attributes of maternal role were considered nurturing, protecting, caretaking, and managing household affairs.  The consequences were the awareness of neonatal status, balanced fulfillment of multiple roles, maternal role strain, and role conflict. Conclusion: The present analysis identified the common attributes, antecedents, and consequences of maternal role. In addition, this analysis differentiated the concept from similar and related concepts that led to greater clarification of maternal role in nursing and midwifery. Considering the maternal role, this conceptual structure provided clarity and contributed to the body of knowledge representing a method to guide nurses and midwives in their practice and research.